Value of transbronchial needle aspiration combined with a rapid on-site evaluation of cytology in the diagnosis of pulmonary lesions - Liang, Long; Duan, Hongxia; Zhu, Huiyuan; Yang, Huiqiong; Li, Xuan; Wang, Changhui; Xie, Shuanshuan (Frontiers in Medicine, 2022)
Background The diagnostic value of rapid on-site evaluation (ROSE) of cytology during endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) remains controversial. The purpose of this study was to validate the value of ROSE during the EUBS-TBNA procedure in the diagnosis of pulmonary lesions (PLs). Methods Enrolled in this study were 260 patients with nodules, masses, cavities, or inflammatory lesions on pulmonary CT images. They were assigned to undergo EBUS-TBNA with ROSE (n=134) or without ROSE (n=126). The diagnostic results of ROSE during EBUS-TBNA and the final pathologic reports were analyzed and compared by utilizing SPSS21.0 software to evaluate the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). In addition, we further explored whether the ROSE method during EBUS-TBNA would improve the diagnostic yield and reduce the incidence of complications. Results The overall diagnostic yield of EBUS-TBNA for malignant diseases in the ROSE and the non-ROSE group were 29.9% and 11.1%, respectively. The sensitivity, specificity, PPV and NPV of the ROSE method during EBUS-TBNA were 97.4%, 96.9%, 92.5% and 98.90% respectively. The result of the chi-square test effectively proved that ROSE operation during EBUS-TBNA contributes to the diagnosis of malignancy compared with the non-ROSE group (χ2=13.858, P<0.001). The number of punctures in the ROSE group was significantly lower than that in the non-ROSE group (P<0.001). Conclusions ROSE examination during EBUS-TBNA could effectively improve the diagnostic yield of malignant diseases compared with the non-ROSE group and reduce the number of intraoperative punctures, which is a clinical application worth popularizing.